2021
DOI: 10.1002/admt.202100476
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Nanoimpregnation Method for Preparing Paper‐Based Sensors and Actuators

Abstract: Paper‐based advanced functional materials have become the focus of intense research in recent years. Particularly, magnetic papers show strong potential for applications in a wide range of 4.0 technologies including communication, magnetic sensing, electromagnetic filtering, magnetic‐based health care tools, point‐of‐care microfluidic devices, and security. In situ and lumen‐loading, the main methods to prepare magnetoactive papers, have problems such as the rigorous reaction conditions, hard control of deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…All samples reveal the absence of hysteresis, remanence, and coercivity, consistent with the single domain behavior, as room temperature (≈30 °C) is above the blocking temperature and the nanoparticle’s magnetic moment is able to rotate in response to the imposed DC magnetic field. , Additionally, the magnetic saturation of the PVA-Fe 3 O 4 layer (≈39.5 emu·g –1 ) corresponds to 84.4% of the magnetic saturation of pure Fe 3 O 4 (≈46.8 emu·g –1 ), thus showing that the printing process did not substantially affect the wt % of Fe 3 O 4 in the PVA matrix. Additionally, magnetic measurements allowed us to determine the content of Fe 3 O 4 on the multilayer structures, paper/PVA-Fe 3 O 4 @Ag, and PET/PVA-Fe 3 O 4 @Ag (≈58 wt %).…”
Section: Results and Discussionsupporting
confidence: 70%
“…All samples reveal the absence of hysteresis, remanence, and coercivity, consistent with the single domain behavior, as room temperature (≈30 °C) is above the blocking temperature and the nanoparticle’s magnetic moment is able to rotate in response to the imposed DC magnetic field. , Additionally, the magnetic saturation of the PVA-Fe 3 O 4 layer (≈39.5 emu·g –1 ) corresponds to 84.4% of the magnetic saturation of pure Fe 3 O 4 (≈46.8 emu·g –1 ), thus showing that the printing process did not substantially affect the wt % of Fe 3 O 4 in the PVA matrix. Additionally, magnetic measurements allowed us to determine the content of Fe 3 O 4 on the multilayer structures, paper/PVA-Fe 3 O 4 @Ag, and PET/PVA-Fe 3 O 4 @Ag (≈58 wt %).…”
Section: Results and Discussionsupporting
confidence: 70%
“…In order to evaluate the spreading of the produced waxes on the Whatman n°1 cellulose paper, contact angle experiments were conducted with the paper at temperatures of 30 and 80 °C (Figure 3c,d). It is shown that increasing paper substrate temperature leads to an increase of the impregnation of all the waxes, [ 56,57 ] as indicated by the variation of the contact angle from 123.7° ± 2.5° to 5.3° ± 0.6° in the case of neat wax, from 129.6° ± 1.4° to 10.8° ± 1.1° in the case of 5 wt% GNP/Wax and from 136.5° ± 2.8° to 15.7° ± 0.7° in the case of the 20 wt% GNP/Wax. New measurements performed around 4 months later demonstrate the stability of the materials and prints over time, with no relevant contact angle values variations over time (all values being within experimental error).…”
Section: Resultsmentioning
confidence: 99%
“…Various neat wax and GNP/Wax designs with defined dimensions were created, according to the intended application (described in Sections 2.3 and 2.4), using a computer-assisted design software (Sketchup 2017) and printed with a Xerox ColorQube 8880 printer (during printing the cartridge melts at temperature higher than 100 °C) on the Whatman n°1 cellulose paper substrates (uncured samples) (Figure 1g). After printing, the samples were placed on a hot plate for a thermal cure at 100 °C for 5 min, allowing the wax to penetrate the substrates all the way through to the opposing surface (cured samples) [56,57] (Figure 1h).…”
Section: Printing Processmentioning
confidence: 99%
“…Magnetic materials possess peculiar chemical and physical properties including magnetocaloric effect, strong magnetic resonance and responsiveness, and so on. As a result, they play the decisive role in magnetically targeted drug delivery, , thermal therapy for cancer, , separation, , sensors, , magnetic resonance imaging, , and catalysis. , In contrast, mesoporous materials with a pore diameter at range of 2–50 nm according to the IUPAC, exhibit high surface area, regular pore structure, and large pore volume, and demonstrate potential applications in macromolecule adsorption, , separation and purification, , catalysis, , sensor, , and drug delivery and release. , The noncovalent interaction such as electrostatic attraction or hydrogen bonding interaction between a soft template and framework oligomers drives the assembly and the construction of mesoporous materials with regulated and uniform pore size, nanostructure, specific composition, and surface property. Integrating the properties of magnetism and mesoporous structure to prepare yolk–shell structure with magnetic core, intermediate void, and mesoporous shell have aroused intriguing attentions owing to internal magnetic core with superparamagnetic and quick magnetic response speed as well as the cavity and mesoporous shell providing more active sites, channels, and space for transportation, storage, and fixation. …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic materials possess peculiar chemical and physical properties including magnetocaloric effect, strong magnetic resonance and responsiveness, and so on. As a result, they play the decisive role in magnetically targeted drug delivery, 1,2 thermal therapy for cancer, 3,4 separation, 5,6 sensors, 7,8 magnetic resonance imaging, 9,10 and catalysis. 11,12 In contrast, mesoporous materials with a pore diameter at range of 2−50 nm according to the IUPAC, exhibit high surface area, regular pore structure, and large pore volume, and demonstrate potential applications in macromolecule adsorption, 13,14 separation and purification, 15,16 catalysis, 17,18 sensor, 19,20 and drug delivery and release.…”
Section: ■ Introductionmentioning
confidence: 99%